2017
DOI: 10.12688/f1000research.11243.1
|View full text |Cite
|
Sign up to set email alerts
|

In vivo genome editing in animals using AAV-CRISPR system: applications to translational research of human disease

Abstract: Adeno-associated virus (AAV) has shown promising therapeutic efficacy with a good safety profile in a wide range of animal models and human clinical trials. With the advent of clustered regulatory interspaced short palindromic repeat (CRISPR)-based genome-editing technologies, AAV provides one of the most suitable viral vectors to package, deliver, and express CRISPR components for targeted gene editing. Recent discoveries of smaller Cas9 orthologues have enabled the packaging of Cas9 nuclease and its chimeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
104
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(111 citation statements)
references
References 160 publications
(240 reference statements)
0
104
0
1
Order By: Relevance
“…To overcome this problem, a novel strategy was introduced using the smallest Cas9 orthologue derived from Campylobacter jejuni (CjCas9), which was able to successfully reduce VEGFA gene expression in mice with age‐related macular degeneration. In this regard, a new pathway was discovered for the in vivo treatment of age‐related macular degeneration (Table ) …”
Section: Introductionmentioning
confidence: 99%
“…To overcome this problem, a novel strategy was introduced using the smallest Cas9 orthologue derived from Campylobacter jejuni (CjCas9), which was able to successfully reduce VEGFA gene expression in mice with age‐related macular degeneration. In this regard, a new pathway was discovered for the in vivo treatment of age‐related macular degeneration (Table ) …”
Section: Introductionmentioning
confidence: 99%
“…As such, we have previously shown that rAAV-and zinc-finger nuclease (ZFN)-mediated liver targeting can correct disease phenotypes in neonatal and adult mouse models, a process currently under clinical investigation [18][19][20][21] . Therefore, further development of robust and wide-ranging CRISPR-based technologies for in vivo editing may help to decipher disease mechanisms and offer novel therapeutic options 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…As such, we have previously shown that rAAV-and zinc-finger nuclease (ZFN)-mediated liver targeting can correct disease phenotypes in neonatal and adult mouse models, a process currently under clinical investigation [18][19][20][21] . Therefore, further development of robust and wide-ranging CRISPR-based technologies for in vivo editing may help to decipher disease mechanisms and offer novel therapeutic options 22,23 .Here we revisited the properties of Streptococcus thermophilus type II-A CRISPR1-Cas9 system, a model nuclease of paramount importance to the entire CRISPR field, and engineered a potent RNA-guided nuclease for both in vitro and in vivo applications. S. thermophilus encodes up to two active type II-A systems (CRISPR1 and CRISPR3) that epitomize the instrumental role played by researchers focusing on the biology of CRISPR-Cas systems in the development of genome-engineering tools 5,24 .…”
mentioning
confidence: 99%
“…5 Nonvirally-mediated transient expression of CRISPR components in the retina may reduce safety concerns, although viral delivery systems based on AAV represent the most efficient and safe tools for gene delivery to the retina. Indeed genome editing using the AAV-CRISPR system has been widely reported as efficient, safe, and precise in more than 30 published studies in mouse models 6 of diseases associated with the eyes, muscle, liver, heart, and lung. Despite the great potential of AAV vectors, their relatively small packaging capacity represents a limitation for delivering the widely used Streptococcus pyogenes Cas9 (SpCas9) together with guide RNAs (gRNAs) and large transgenes.…”
mentioning
confidence: 99%